Human tumor necrosis factor produced by human B-cell lines: synergistic cytotoxic interaction with human interferon. - Williamson, B D (1983)
Human cell lines of hematopoietic origin were tested for production of tumor necrosis factor (TNF). B-cell lines transformed by Epstein-Barr virus release a factor (referred to as hTNF) that is cytotoxic for mouse L cells sensitive to mouse TNF but not for L cells resistant to mouse TNF. Exposure to 4 beta-phorbol 12 beta-myristate 13 alpha-acetate augmented production of hTNF. hTNF activity was not found in supernatants of cell lines of T-cell, monocytic, or promyelocytic origin. Partially purified hTNF has a molecular weight of approximately 70,000, has no interferon activity, is acid labile, is destroyed by heating at 70 degrees C for 1 hr, induces cross-resistance to mouse TNF in vitro, and causes hemorrhagic necrosis of Meth A mouse sarcoma in the standard in vivo mouse TNF assay. Tests with a panel of 23 human cancer cell lines showed that hTNF is cytotoxic for 7 cell lines, cytostatic for 5, and has no effect on 11. Comparative studies with human alpha, beta, and gamma interferons indicated that sensitivity to hTNF and interferon can be distinguished. Combined treatment with hTNF and alpha or gamma interferon resulted in a synergistic cytotoxic effect.